From the scientific method to the clinical method: theoretical considerations - Roberto Hernández Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
The scientific method is a general method composed of several stages necessary for the development of any scientific research. It is the focus to approach reality and to study natural phenomenon, reality itself and thoughts in order to find their essence and interrelationships. The clinical method is the particular application of the scientific method and in the present economic conditions its use is crucial because of the advantages that it reports from this point of view, as well as for the wellbeing of the patient.